An Internet of Things-enabled model-based approach to improving the energy efficiency of aluminum die casting processes. (1st July 2020) - Liu, Weipeng; Peng, Tao; Tang, Renzhong; Umeda, Yasushi; Hu, Luoke
Abstract: The demand for aluminum products is expected to continually increase. Die casting is an important technology for processing aluminum products. It is energy-intensive and its melting and holding sub-processes consume large amounts of energy, but in low energy efficiency. Therefore, improving their energy efficiency can significantly reduce energy costs and environmental impact. Based on an in-depth field survey of die casting factories, two obstacles hindering the melting and holding energy efficiency improvement were identified: 1) the determination of optimal furnace operation parameters in the production planning stage, and 2) the timely adjustment of furnace operation parameters when an incident occurs in the production stage. An Internet of Things-enabled model-based approach, including a parameter optimization model and energy-aware incident control strategy, was proposed to address these two issues. The proposed approach was validated in a die casting factory. Optimizing the furnace melting rate and maximum holding height saved 5%–9% cost, product stock was reduced by approximately 3.6% with the online adjustment of the furnace melt-stoppage time, and holding energy consumption was reduced by approximately 2% with the online control of the furnace standby mode. It was revealed that the practical value of the proposed approach was significant for industrial applications. Highlights: Two issues of energy efficiency improvement of die casting were identified. Parameter optimization model and incident control strategies were introduced. 5%–9% energy and material cost was saved using the parameter optimization model. 3.6% stock and 2% holding energy were reduced by the incident control strategies. The proposed approach was practically significant for industrial applications.